DETERMINANTS OF MARKET PARTICIPATION AMONG ARABLE CROP FARMERS IN KWARA STATE, NIGERIA: EVIDENCE FROM MAIZE AND SORGHUM FARMERS - Ayodeji, F.O.; Ambali, O.Y.; Mahmud, H. U. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
The study examined the level and determinants of market participation among arable crop farmers in Kwara State, Nigeria, with a focus on maize and sorghum production. A multi-stage sampling technique was used in selecting 91 respondents for the study. Data were collected through structured questionnaires administered to maize and sorghum farmers using face-to-face interviews and analysed using both descriptive and inferential statistics. The results revealed maize farmers recorded a mean commercialization index of 54.21, with 47.2% falling within the 51–60% market participation category. Similarly, sorghum farmers had a mean index of 52.58, with 39.5% within the same commercialization range. The Probit regression results indicated that maize market participation was significantly influenced by age (p < 0.05), household size (p < 0.05), level of education (p < 0.05), access to credit (p < 0.01), and farm size (p < 0.05). For sorghum farmers, significant determinants included access to credit (p < 0.05), farm size (p < 0.01), association membership (p < 0.05), access to extension services (p < 0.05), and distance to market (p < 0.05).The study concludes that market participation among arable crop farmers in Kwara State is moderately commercialized. Maize participation was mainly influenced by age, household size, education, access to credit, and farm size, while sorghum participation was driven by credit access, farm size, association membership, extension services, and distance to market. The study therefore recommends improved access to credit, stronger extension support, enhanced cooperative participation, and better rural market infrastructure to promote commercialization.